ANALISIS POSTUR KERJA MANUAL MATERIAL HANDLING (MMH) MENGGUNAKAN RAPID UPPER LIMB ASSESSMENT (RULA) DI PT.XYZ : Indonesia - whydiantoro whydiantoro; Dony Susandi; intan kusumadewi (Universitas Majalengka, 2021)
The use of human labor in the industrial world in Indonesia is still very dominant, especially in Manual Material Handling (MMH) activities. The activity of bending and twisting in the workplace while doing MMH should be reduced or even if possible this activity should be eliminated because this attitude is prone to causing disorders of the musculoskeletal system. Considering that MMH activities have a vital role in the work carried out in the production process section, therefore the researcher will conduct an analysis of the Manual Material Handling (MMH) work posture using the Rapid Upper Limb Assessment (RULA). RULA is a work posture research method to investigate disorders of the upper limbs. The results of the work posture analysis based on the results of the assessment using the RULA method stated that all manual material handling activities assessed above required corrective action or efforts. In the shuttle area, the final score for the action category obtained is 7 with a high risk level and the action that must be taken is action now. In the Pirn Winder area, the final score for the action category obtained is 6 with a moderate risk level and the action that must be taken is action in the near future. In the vacuum heat setter area, the final score for the action category obtained is 7 with a high level of risk and the action that must be taken is action now.